Silica Nanowire Growth on Coscinodiscus Species Diatom Frustules via Vapor–Liquid–Solid Process. Issue 47 (4th October 2018) - Li, Aobo; Zhao, Xiaoguang; Anderson, Stephan; Zhang, Xin
Abstract: Diatom frustules are a type of porous silicon dioxide microparticle that has long been used in applications ranging from biomedical sensors to dye‐sensitized solar cells. The favorable material properties, enormous surface area, and enhanced light scattering capacity support the promise of diatom frustules as candidates for next generation biomedical devices and energy applications. In this study, the vapor–liquid–solid (VLS) method is employed to incorporate silica nanowires on the surface of diatom frustules. Compared to the original frustule structures, the frustule–nanowire composite material's surface area increases over 3‐fold, and the light scattering ability increases by 10%. By varying the gold catalyst thickness during the VLS process, tuning of the resultant nanowire length/density is achieved. Through material characterization, it is determined that both float growth and root growth processes jointly result in the growth of the silica nanowires. From a thermodynamics point of view, the preferential growth of the silica nanowires on frustules is found to have resulted from the enormous partial surface area of gold nanoparticles on the diatom frustules. The frustule–nanowire composite materials have potential applications in the development of novel biomedical sensing devices and may greatly enhance next generation solar cell performance. Abstract : Silicon dioxide nanowires are incorporated on the surface of diatom frustules, drastically enhancing the surface area and light scattering properties of diatom frustules. With thermodynamics theories, the preferential growth of nanowires on the surface of diatom frustules is analyzed. The resultant diatom–nanowire composite material can be readily used in a wide range of applications that require silicon dioxide nanostructures.